PERBANDINGAN ANTARA FAKTUR PAJAK MANUAL DAN E-FAKTUR - Richard, Amsal; Siswoatmodjo, Sistomo; Tampubolon, Emma (Fakultas Ekonomi Universitas Kristen Indonesia, 2017)
The main purpose of this research is to find out the changes made when old invoice system is no longer in use and now people use e-faktur, the new invoice that basic on internet. To find out the changes, the writer do comparison between the old and new invoices. This research was conducted at PT Filtras Indonesia. This research was using field study system which gather data from some employers that work at PT Filtras Indonesia. The result of this research shows that almost of the changes are positive, meaning the implementation of e-faktur was a success.Key words: e-faktur, invoice system change, invoice comparison